DJ Algorytm – cyfrowa sugestia muzyczna jako substytut własnego wyboru - Nożyński, Szymon (Neodidagmata, 2018)
The article attempts to find answers to questions about the autonomy of choice associated with new media services focused mainly on digital music streaming. Today, the role of the guide’s journalist partly taken over by algorithms that are based on data provided by users of all types of music services. Moreover, in the „algorithm – listener” system, the so-called „curator” is important, which is someone between a music journalist and a gatekeeper, depending on the level of advancement and range of services. The algorithm that more and more often performs functions related to making a choice can both help and limit, suggest and laze, enrich and disturb.